2013
DOI: 10.1037/a0031390
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pain and the interpersonal theory of suicide.

Abstract: These findings suggest that the interpersonal theory is relevant to understanding elevated rates of suicidal ideation among people with chronic pain, and may have broader applicability to other populations with chronic illness or disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 24 publications
2
45
0
Order By: Relevance
“…This SPB may have a negative impact upon psychological wellbeing and is predictive of suicidal ideation [56]. Feelings of SPB are important to target in pain management, particularly due to its positive correlation with pain intensity, depression and anxiety [57,58], and its impact on the well-being of patient friends and families, who are at increased risk of suffering depression and anxiety [59]. Outpatient social support through the use of peer and family mentoring discussions may therefore be informed by staff knowledge of ongoing pain, in order to improve such social support.…”
Section: Discussionmentioning
confidence: 99%
“…This SPB may have a negative impact upon psychological wellbeing and is predictive of suicidal ideation [56]. Feelings of SPB are important to target in pain management, particularly due to its positive correlation with pain intensity, depression and anxiety [57,58], and its impact on the well-being of patient friends and families, who are at increased risk of suffering depression and anxiety [59]. Outpatient social support through the use of peer and family mentoring discussions may therefore be informed by staff knowledge of ongoing pain, in order to improve such social support.…”
Section: Discussionmentioning
confidence: 99%
“…22,23,27,28,31 Among the more consistent individual correlates of SI (ie, variables that have been identified in more than a single study) are previous suicide attempts, 24,25 longer pain duration, 31,32 depressive symptoms, 23,26,28-30,32 pain catastrophizing, 23,25,32 pain-related interference with activities, 23,25 low use of coping self-statements, 23,25 and the sense that one has become a burden to others. 26,32,33 In some studies, 23,25,29 but not all, 26,28,32 SI has also been associated with greater pain intensity. Some of these risk factors represent historical facts that cannot be changed; however, others are potentially modifiable with appropriate intervention.…”
mentioning
confidence: 93%
“…Depending on the study sample and method of assessment, at least passive thoughts of death or suicide have been reported by 14.1% to 41.5% of pain clinic attenders, [22][23][24][25][26][27][28][29][30] whereas more active SI has been expressed by 1.2% to 16.6%. 22,23,27,28,31 Among the more consistent individual correlates of SI (ie, variables that have been identified in more than a single study) are previous suicide attempts, 24,25 longer pain duration, 31,32 depressive symptoms, 23,26,[28][29][30]32 pain catastrophizing, 23,25,32 pain-related interference with activities, 23,25 low use of coping self-statements, 23,25 and the sense that one has become a burden to others. 26,32,33 In some studies, 23,25,29 but not all, 26,28,32 SI has also been associated with greater pain intensity.…”
mentioning
confidence: 99%
“…A total score was created by summing the responses. The PCS correlates with measures of pain intensity, mood, functional interference, and SI 13 and has excellent test-retest reliability. 34 In the current study, the PCS demonstrated excellent internal consistency (α = 0.93).…”
Section: Pain Catastrophizingmentioning
confidence: 99%
“…2,10,11 In chronic pain, it has been associated specifically with selfreports of SI. 9,12,13 The second body of research is grounded in the interpersonal theory of suicide, 14,15 which proposes that serious SI depends on the emergence of two psychological precursor conditions, namely, thwarted belongingness and perceived burdensomeness. Thwarted belongingness refers to an unmet need for a sense of social connection and is reflected in issues such as isolation, loneliness, and impoverished social networks.…”
Section: Introductionmentioning
confidence: 99%